2020
DOI: 10.1016/j.techfore.2020.120195
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric correlation and hedging effectiveness of gold & cryptocurrencies: From pre-industrial to the 4th industrial revolution✰

Abstract: Highlights The effects of gold on stock market are asymmetric in most of the cases. Cryptocurrency does not affect stock market significantly. Correlations between stock/gold and stock/cryptocurrency pairs are found to be positive in most cases. Neither gold nor cryptocurrency acts as a good instrument for hedging stock market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 50 publications
(60 reference statements)
1
37
0
Order By: Relevance
“…Some studies considered cryptocurrencies and gold within the same empirical investigation (see Klein, 2017 ; Lucey and Li, 2015 ) and found that cryptocurrencies are not stable over time ( Klein et al, 2018 ; Corbet et al, 2020b ). A recent study by Thampanya et al (2020) raised concerns about the hedging ability of both gold and cryptocurrencies with respect to the stock market, whereas, in a contemporaneous study, Huynh et al (2020) argued that although the fourth industrial revolution has created new investment opportunities in the form of technology indexes and cryptocurrencies, the significance of traditional assets such as gold has not been diminished. Given that the debates regarding hedge effectiveness and the safe haven characteristics of various asset classes are still unsettled, the COVID-19 pandemic has given it a new context.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies considered cryptocurrencies and gold within the same empirical investigation (see Klein, 2017 ; Lucey and Li, 2015 ) and found that cryptocurrencies are not stable over time ( Klein et al, 2018 ; Corbet et al, 2020b ). A recent study by Thampanya et al (2020) raised concerns about the hedging ability of both gold and cryptocurrencies with respect to the stock market, whereas, in a contemporaneous study, Huynh et al (2020) argued that although the fourth industrial revolution has created new investment opportunities in the form of technology indexes and cryptocurrencies, the significance of traditional assets such as gold has not been diminished. Given that the debates regarding hedge effectiveness and the safe haven characteristics of various asset classes are still unsettled, the COVID-19 pandemic has given it a new context.…”
Section: Introductionmentioning
confidence: 99%
“…This surge in Bitcoin prices, observed during the COVID-19 pandemic, has been accompanied by a significant amount of literature investigating whether cryptocurrencies, particularly the bitcoin, might serve as a refuge during a period of turmoil, such as the ongoing health crisis (Huynh et al, 2020 ; Paule-Vianez et al, 2020 ; Thampanya et al, 2020 ; Mnif et al, 2020 ; Madani et al, 2021 , among others). In this context, it might be important to analyse and propose further insights in terms of volatility modelling and cryptocurrency market forecasting, especially during crisis periods such as the COVID-19 pandemic, allowing investors and hedgers to minimize risks through portfolio diversification and develop appropriate hedging positions, and assist policymakers in formulating regulatory policies by refining the asset prices volatility prediction for risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we focus thus on returns generated by Eq (12) and seek to optimize the investment trajectories based on them. Different approaches to portfolio optimization and hedging using GARCH type models and asymmetric correlations can be found in, for example, [ 35 , 36 ].…”
Section: Volatility Modelsmentioning
confidence: 99%